Incidence and Management of Arterial Anomalies in Patients Undergoing Pancreaticoduodenectomy - Perwaiz, Azhar; Singh, Amanjeet; Singh, Tanveer; Chaudhary, Adarsh (JOP. Journal of the Pancreas, 2016)
Context Pancreaticoduodenectomy entails ligation of vascular arcades arising from the celiac and superior mesenteric arteries. These are known to have anatomical variations. Objective This study was aimed at analyzing the spectrum of arterial anomalies and their clinical impact on the procedure itself. Patients The study includes 200 consecutive patients who underwent a pancreaticoduodenectomy between September 2003 and May 2009 after excluding those having distant metastases or local unresectability. Main outcome measures The records of the patients were studied to assess the incidence of arterial anomalies and the operative complexities involved in a pancreaticoduodenectomy. Results Fifty-three patients (26.5%) had arterial anomalies. The complexity of the surgery was determined by the course of these arteries. The mean duration of surgery was 420±32.0 minutes in patients with arterial anomalies versus 370±38.5 minutes in those with a normal arterial anatomy (P= 0.005). Fifty-one out of 53 (96.2%) patients underwent pancreaticoduodenectomy with negative resection margins. The pancreaticoduodenectomy was abandoned in two cases due to patient- and tumor-related factors. Conclusion During pancreaticoduodenectomy, arterial anomalies can increase operative complexity but do not usually compromise the safety of the procedure or its oncological outcome. Image: Celiac artery stenosis with tortuous pancreaticoduodenal arcade.